To solve the equation \( -9 + (x - 3)^2 - 4 = -4 \), we can start by simplifying the equation.
-
First, we can combine the constants on the left side: \[ -9 - 4 + (x - 3)^2 = -4 \] This simplifies to: \[ -13 + (x - 3)^2 = -4 \]
-
Next, we can add 13 to both sides: \[ (x - 3)^2 = -4 + 13 \] Which simplifies to: \[ (x - 3)^2 = 9 \]
-
Now, we take the square root of both sides: \[ x - 3 = \pm 3 \]
-
This gives us two separate equations:
- \( x - 3 = 3 \)
- \( x - 3 = -3 \)
-
Solving these equations:
- For \( x - 3 = 3 \): \[ x = 3 + 3 = 6 \]
- For \( x - 3 = -3 \): \[ x = 3 - 3 = 0 \]
Thus, the solutions are \( x = 6 \) and \( x = 0 \).
Now, let's match these solutions to the available options: None of the provided responses in your question match \( {6, 0} \).
If you'd like to clarify or present different options, please do!